2022
DOI: 10.1177/23998083221144321
|View full text |Cite
|
Sign up to set email alerts
|

Fractured smart cities: Missing links in India’s smart city mission

Abstract: The postscripts of smart cities have been written before its prelude. Inserting smart technologies in infrastructure to improve urban environments, smart cities emphasize data-driven approaches and evidence-based planning. While it asks for production of new vocabularies, new ways of thinking, and proposes new methodologies, smart cities have trivialized baseline surveys. The insignificance to baseline survey hides the existing and functioning cities and leads to appropriation of “smart in the box” technologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The Smart Cities Mission, however, has been controversial in several ways. First, the language of “smart cities” and the presumption of homogeneous technology-led solutions ignore the reality of inequity and poor access to basic services on the ground, creating a normative disconnect (Singh & Upadhyay, 2022). Second, the changes can be argued to represent the latest manifestation of a neo-liberal shift in Indian politics and society that sees the creation of elite spaces with bespoke governance arrangements (Basu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Smart Cities Mission, however, has been controversial in several ways. First, the language of “smart cities” and the presumption of homogeneous technology-led solutions ignore the reality of inequity and poor access to basic services on the ground, creating a normative disconnect (Singh & Upadhyay, 2022). Second, the changes can be argued to represent the latest manifestation of a neo-liberal shift in Indian politics and society that sees the creation of elite spaces with bespoke governance arrangements (Basu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Bibri and Krogstie [ 16 ] suggested that: (1) smart cities focus on modern information and communication technologies and efficient solutions without considering the design aspects of sustainability, (2) smart cities are mainly dedicated to achieving smart goals rather than development goals, and (3) the link between the smart city concept and environmental sustainability is weak. Further, the standardized smart city concept masks the complexity and heterogeneity of cities and proposes solutions that do not fit the existing urban context [ 17 ].…”
Section: Introductionmentioning
confidence: 99%